Arsenic Bioavailability Assessment - Former Pipfruit Orchards on Mapua and Ranzau Soils, Tasman District (Massey University and Tasman District Council) - Bull D; Lines W (Envirolink (envirolink.govt.nz), 2016)
Tasman District Council (TDC) commissioned Massey University to investigate oral bioavailability of arsenic at former orchard sites selected by TDC, and prepare a ‘Tier II’ health risk assessment for sampled soil types. Massey, in turn, commissioned HAIL Environmental Ltd (HAIL Environmental) to assist with this work as a specialist contaminated land subcontractor with experience in bioavailability assessment. SEM analysis was carried out at Massey. This report of the work overseen by Massey (Dr Nick Kim) presents HAIL Environmental’s results and conclusions. .